Designing Information System of Website-Based Presence for Online Seminar in Postgraduate School of Universitas Sebelas Maret Surakarta: Perancangan Sistem Informasi Presensi Berbasis Website Untuk Kegiatan Seminar Online Di Sekolah Pascasarjana Universitas Sebelas Maret Surakarta - Purwanto, Joko; Naury, Chairullah; Pantjarani, Ari (RADIANT: Journal of Applied, Social, and Education Studies, 2023)
The problem faced in conducting online seminars at the Postgraduate School of Sebelas Maret University Surakarta (UNS) is the difficulty of recording the attendance of online seminar participants. Currently, the process of recording attendance data for online seminar participants is done using the Google Form application. The use of Google Forms for data collection of seminar participants is considered inefficient. This is because the online seminar committee is still copying data from the Google Form to be compiled into a report on the implementation of the online seminar. Based on the description of the background above, it can be formulated the problem to be solved in this research is "How to design a website-based attendance information system for online seminar activities at the UNS Graduate School". Limitations The problem that the author discusses in this study focuses more on the process of recording attendance data for online seminars organized by the UNS Graduate School. The method used to design a presence information system using the System Development Life Cycle (SDLC) with the Waterfall model. The programming language used in designing the presence information system is PHP Native, while the MySQL database is used for data storage. It is hoped that with the design of this attendance information system, it can help organizers of online seminars at the UNS Graduate School, both at national and international levels, to facilitate the process of taking attendance of seminar participants.